Evaluation of glass welding by ultrashort pulse laser - Mohid, Zazuli (2008)
It is considered that fusion welding should be the most promising technique in glass joining, since joining can be accomplished without any intermediated layer and mechanical contact. High precision, small heat-affected zone (HAZ) and small shock-affected zone (SAZ) makes ultra-short pulsed laser capable to perform the process with minimal damages to the surrounding area. However, there are still a lot of things to be clarified in this process, since glass materials are veiy sensitive to temperature gradients and available in different thermal properties. In this study, molten zones created by high ultra-short pulsed laser in borosilicate glass (Schott D263) and fused silica were evaluated. Laser irradiation was done inside the glass some micrometers below the top surface under various processing conditions. Molten zone was observed visually and its strength was measured using bending test. Actual fusion welding of two glass plates was also successfully demonstrated and evaluated by strength measurement. The influence of polarization, feed rate v, incident laser power Win and pulse repetition rate Rp to molten zone strength and appearance were discussed. Main conclusions in this study are as follows:- a) There was no obvious influence to the molten zone appearance by the difference of beam polarizations. b) Incident laser power played the most important role in controlling molten zone size. Molten zone size increased with the increment of laser power. c) Cracks and bubbles were effectively reduced by selecting the proper pulse repetition rate. Low pulse repetition rate led to cracking at the surrounding area of molten zone and high pulse repetition rate caused cracking in the bottom area of molten zone. d) Measurement of mechanical strength had proven that low feed rate offered wider applicable pulse repetition rate with no fatal strength decrement of molten zone by ultra-short pulse laser. Keywords: Ultra-short pulse laser, borosilicate glass, fused silica, molten zones, heat effected zone (HAZ), fusion welding, feed rate, polarization, pulse repetition rate.